Implementasi Model Pembelajaran Ekonomi Berbasis Kompetensi Dengan Pendekatan Kontekstual - Tejo Nurseto (Jurnal Ekonomi dan Pendidikan, 2005)
This research was intended to know the extent of contextual approaches (Contextual Teaching and Learning) able to overcome practical problems in compliance with the students ability to construct a concept/meaning from what they learned. The scope of this inquiry included the implementation of contextual approaches to the subject of Introduction to Economic Science in Economic Cooperative Education Study Program of Business Education Department of Faculty of Social Science of Yogyakarta State University. This was a participatory action research. The action research was implemented in the academic years of 2003/2004 for the subject of Introduction to Economic Science. This research was conducted in several steps as follows: Planning, Action Implementation, Control and Evaluation, and Analysis and Reflection. The results show that: (1) in the first cycles, the ways of answering questions, answers the students present are not qualified, the frequency of expressing opinions tends to be minimum, and the interaction among students are low. Due to lack of time in accordance with the grouping and student classification spending too much time, 2 CTL methods can be used to improve: the students participation in discussing the results of the discussion conducted, the students way in revealing describing oral description review, the students capability in constructing concept/meaning. In applying CTL, it is found some weaknesses as follows: the frequent use of CTL method makes the students saturated, the use of CTL method requires more cost, it is good for creating media or doing observation, for the students with high level of learning motivation it is exciting for they regard that they have chance to deliver more opinions, and those with low level of learning motivation it makes them passive and talking to themselves (not interested).